Development and Validation of a Questionnaire to Assess Social Participation of High Risk-Adults in Germany During the COVID-19 Pandemic - Schröder, Dominik; Heesen, Gloria; Heinemann, Stephanie; Hummers, Eva; Jablonka, Alexandra; Steffens, Sandra; Mikuteit, Marie; Niewolik, Jacqueline; Overbeck, Tobias R.; Kallusky, Jonathan; Müller, Frank (Frontiers in Public Health, 2022)
Background: Restrictions to contain the COVID-19 pandemic affects the social participation of people worldwide. Especially those at high risk for a severe disease tend to abstain from social gatherings. While there are a few questionnaires to measure social participation in elderly or chronic patients, a valid survey instrument that includes pandemic-related social participation is needed. Methods: We developed a social participation questionnaire that aims to assess pandemic-related restrictions in social participation. Items were developed using a theory and literature-based approach and then compiled in a discursive process involving experts and lay people. This was followed by the validation of the questionnaire through a cross-sectional survey on 431 individuals. Items with low item-total correlations and low factor loadings using exploratory factor analysis [EFA] were excluded. Using EFA on the remaining items, the factor structure was retrieved and tested with a confirmatory factor analysis [CFA]. Internal consistency was assessed with Chronbachs α. Results: Initially, 27 items were developed which were used for validation. Seven items were excluded due to low item-total correlations and factors loadings. EFA of the remaining 20 items revealed four factors which were identified as domains “active social participation”, “wellbeing”, “restrictions”, and “worries”. CFA showed an acceptable goodness of fit using the four-dimensional structure. Chronbachs α of 0.82 indicate good internal consistency. Correlation analysis showed an association between the developed questionnaire and previously-established participation and mental health scales. Conclusion: This study suggests that our 20 item questionnaire is of high reliability and validity and can be used to measure social participation during a pandemic.